2023
DOI: 10.3389/fendo.2023.1026040
|View full text |Cite
|
Sign up to set email alerts
|

Sodium glucose co-transporter 2 (SGLT2) inhibition via dapagliflozin improves diabetic kidney disease (DKD) over time associatied with increasing effect on the gut microbiota in db/db mice

Abstract: BackgroundThe intestinal microbiota disorder gradually aggravates during the progression of diabetes. Dapagliflozin (DAPA) can improve diabetes and diabetic kidney disease(DKD). However, whether the gut microbiota plays a role in the protection of DAPA for DKD remains unclear.MethodsTo investigate the effects of DAPA on DKD and gut microbiota composition during disease progression, in our study, we performed 16S rRNA gene sequencing on fecal samples from db/m mice (control group), db/db mice (DKD model group),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
(71 reference statements)
2
5
0
Order By: Relevance
“…The dysfunction of DN in our study is compatible with previous studies using RNA‐seq demonstrating that glucolipid metabolic disorders characterized by insulin resistance, glucolipid toxicity, oxidative stress, and dysbacteriosis have become a very common metabolic defect closely associated with DN 7,14–19 . Previous research results by 16S rRNA gene sequencing on fecal samples suggested that DAPA improved DN possibly associated with the effect on the bile acid homeostasis and its antioxidation effect 13 . In theory, changed metabolism induced by altered microbiome composition can enter circulation and thereby impact peripheral tissue metabolism.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The dysfunction of DN in our study is compatible with previous studies using RNA‐seq demonstrating that glucolipid metabolic disorders characterized by insulin resistance, glucolipid toxicity, oxidative stress, and dysbacteriosis have become a very common metabolic defect closely associated with DN 7,14–19 . Previous research results by 16S rRNA gene sequencing on fecal samples suggested that DAPA improved DN possibly associated with the effect on the bile acid homeostasis and its antioxidation effect 13 . In theory, changed metabolism induced by altered microbiome composition can enter circulation and thereby impact peripheral tissue metabolism.…”
Section: Discussionsupporting
confidence: 91%
“…Due to failed energy utilization, multiple degradation pathways were activated and gene expression pathways were inhibited, as our conjoint analysis of ATAC‐seq and RNA‐seq data in CG vs Controls and two conjoint analyses reversed pathway results also all showed. After DAPA administration, we observed that the weight in TG gradually increased consistent with previous research, 9,12,13 despite studies showed that DAPA could reduce body weight in wt mice. We suppose that weight gains after DAPA intervention, the sign of disease status improvement, appear to manifest as improved energy utilization and increased gene expression suggested by several enrichment results in TG versus CG.…”
Section: Discussionsupporting
confidence: 90%
“…18,24 However, the mechanisms by which SGLT2 inhibitors attenuate liver fibrosis, especially in addition to their hypoglycemic effects, remain unclear and need to be further explored. In the past decade, many studies have found that SGLT2 inhibitors can improve various diseases, such as diabetic kidney disease 25 and atherosclerosis, 14 by modulating gut microbiota, suggesting that gut microbiota might also play an important role in their alleviation of liver fibrosis. The intestinal flora is now considered a novel virtual metabolic organ that maintains homeostasis in the host.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental models of diabetes, microbiota-derived phenyl sulfate (PS) is associated with the progression of albuminuria ( Kikuchi et al., 2019 ). Several recent studies have shown that regulating gut microbiota dysbiosis and improving intestinal barrier function can effectively reduce uremic toxin levels and serum proinflammatory mediators [such as tumor necrosis factor-α, interleukin (IL)-1β, and IL-18], thereby delaying the progression of DN ( Han et al., 2023 ; Shi et al., 2023 ; Wang et al., 2023 ; Wu et al., 2023 ). These studies indicate that gut microbiota disorders play an essential role in the development of DN, and further exploration is needed to diagnose or treat DN by targeting the composition of gut microbiota ( Figure 1 ).…”
Section: Gut Microbiota In Dn Patientsmentioning
confidence: 99%
“…Diabetic nephropathy (DN) is one of the common microvascular complications, characterized by structural and functional damage to the kidneys ( Wu and Huang, 2023 ). Clinical manifestations include massive proteinuria, hypertension, and edema, and it is one of the main causes of end-stage renal disease (ESRD) ( Wu et al., 2023 ). At present, the diagnosis of DN depends on a decreased glomerular filtration rate (GFR) or increased urinary albumin excretion (UAE), but these changes are not unique to DN, and the diagnostic sensitivity and specificity in the preclinical stage of diabetic kidney damage are also limited ( Oshima et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%